ISSUE OF TRANSGENDER RIGHTS FROM THE VIEWPOINT OF ARUNDHATI ROY’S THE MINISTRY OF UTMOST HAPPINESS - Chaturvedi, Devesh Kumar; Sharma, Sheeba Himani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
A transgender person is referred to as a hijra in India. In India, hijra, the third gender, is connected to social-religious purity. People find it difficult to acknowledge the reality of hijra. In addition, the transgender protagonist is seen favorably as a key character in this fiction. It is possible to demonstrate that these texts provide further opportunities for emancipation towards the condition. It observes the transgender concern in relation to desire and connection. Transgender persons experience frequently, prevents them from exercising their fundamental right to an education and a normal life.